Statistical Cluster Points of Subsequences of Double Sequences - Miller, Harry I. (Sarajevo Journal of Mathematics, 2024)
The main result of this paper is the double sequence analogue of a theorem about cluster points of single sequences that has recently submitted for publication [8]. Namely, we show here that if x is a double sequence then Γ_x (the set of statistical cluster points of x) equals Γ_y (the set of statistical cluster points of y) for "almost all" subsequences y of x.